THE DEVELOPMENT OF LONG DISTANCE GUIDELINES MODEL FOR GOVERNMENT EMPLOYEES CANDIDATES - Ahmad, Andy; Ahmad, Andy; Muslim, Suyitno; Situmorang, Robinson (International Journal of Psychosocial Rehabilitation, 2020)
Education in Indonesia is experiencing rapid development, people who want to serve the country of Indonesia are increasing, and one indicator that can be seen is the number of registrants in the selection of candidates for civil apparatus (ASN). The number of state civil apparatus in 2018 totaled 4,351,490. Meanwhile the total population of Indonesia in 2019 was reported from 266.91 million. Seeing the number of ASNs in Indonesia, there is a large gap however, to become an ASN in Indonesia must pass a basic competency selection test that is general intelligence, a national insight test and personality characteristics test, for each opening applicants can study in tutoring. The use of long-distance models is a solution to help participants who are geographically separated in several islands in Indonesia. The method in this study is qualitative. The learning design using ADDIE and distance learning guidance models using E-Learning with the application of google classroom, web-based, youtube and google form.